The Relationship between a Wife's Satisfaction in the Iddah Period with Marriage and Divorce - Nurohim, Muhammad; Pasaribu, Yusuf Hanafi; Asmaiyani, Asmaiyani (Fakultas Syariah UIN Sulthan Thaha Saifuddin Jambi, Indonesia, 2021)
The purpose of this study is to examine the relationship between iddah living with marriage and divorce. The specification of this research is a descriptive analytical law research. The type of data used in this study is secondary data sourced from the library, such as primary legal materials, namely documents and any statutory regulations that are binding and determined by the competent authorities relating to the obligation of living during the iddah period. Plus secondary legal materials and tertiary legal documents. The data collection tool used in this research is a document study by tracing legal materials in the library. Then analyzed qualitatively. The results of this study indicate that the iddah of the ex-wife can only be requested after the divorce from a marriage that is recognized as valid.